Integrating GIS and Augmented Reality in Flood Disaster Education: Effects on Students’ Spatial Literacy and Preparedness - M Iqbal Liayong Pratama; Rusiyah Rusiyah; Wiwin Kobi; Hamengkubuwono Hamengkubuwono; Indrawan Indrawan (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study investigates the effectiveness of GIS and augmented reality (AR) supported immersive flood learning in enhancing students’ spatial literacy and flood preparedness within secondary geography education. Methodology: A quasi experimental pretest–posttest control group design involved 107 Grade XI social science students from six senior high schools in Gorontalo City, Indonesia. The experimental group received GIS and AR supported immersive learning, while the control group received conventional instruction. Data were collected using a 40 item test measuring spatial literacy and flood preparedness. Data analysis employed descriptive statistics, normalized gain analysis, independent sample t tests, and effect size analysis. Main Findings: Students in the experimental group achieved significantly higher posttest scores (M = 84.72, SD = 6.41) than the control group (M = 71.58, SD = 7.24). Statistical testing showed a significant difference between groups (p < .05), while effect size analysis indicated a large practical effect. GIS and AR supported immersive learning improved students’ spatial interpretation, hazard analysis, contextual reasoning, and mitigation planning more effectively than conventional approaches across disaster related geography learning activities. Novelty/Originality of this study: The findings provide empirical evidence that immersive geospatial learning integrating GIS and AR strengthens spatial cognition and disaster preparedness simultaneously within secondary geography education. Unlike previous studies emphasizing technological feasibility, the findings demonstrate the pedagogical role of immersive spatial learning in supporting contextual disaster understanding and environmental reasoning in flood prone educational settings.